(3GdNUGFU (B( (3aj GdfMh (B)s - (3CHh GdaJM YKeGf Hf Lfj GdfMhj,J (B392 (3g` s ((3eMeO eMehO s)
(3ChdgG (B:s
(3HGH ai NdY GdCOdI ef Pdc McGjI jhfS ef bhd GdYQH VQH ef efG Ci GfSGf GfSGfkG hQLd QLdGg s
(3BNQgG (B:s
(3TYQ ddMQH hGdeMQGH ehGba YeQJ GdOfjG hYR GdOjf GfJgi s
(3HChdg agQSs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI eJhSWI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3eJaQbGJs